Morphological variability of evergreen oaks (Quercus) in Turkey (Bangladesh Journal of Plant Taxonomy, 2017)
The genus Quercus L. has a problematic taxonomy because of widespread hybridization among them. Evergreen Quercus contain three species in section Ilex Loudon namely, Q. ilex L., Q. coccifera L. and Q. aucheri Jaub. et Spach in Turkey. Here, two species, Q. coccifera and Q. aucheri are usually confused with each other. However, Q. coccifera and Q. calliprinos are accepted as different species but this subject is still controversial. Morphometric leaf and fruit variations of Q. ilex, Q. coccifera and Q. aucheri in 26 populations were measured for 25 characters. Variations within and among populations of species were detected by cluster analysis and principal component analysis. This study shows that populations of Q. coccifera from the south region of Turkey form a second group within Q. coccifera. Secondly, Q. coccifera show more similarity to Q. aucheri than Q. ilex, and finally there are two groups within Q. coccifera, which may be evaluated as Q. coccifera and Q. calliprinos.